Evaluation of unmet medical need among Japanese patients with type 2 diabetes mellitus and efficacy of Lixisenatide treatment among Asian type 2 diabetes mellitus patients. Issue 1 (January 2016) - Terauchi, Yasuo; Naito, Yusuke; Ikeda, Yukio
Abstract: Aims: This study determined the unmet medical need of basal insulin therapy among type 2 diabetes patients who participated in the ALOHA study. Also a meta-analysis of the GetGoal-Duo1, -L, and -L-Asia trials was conducted to examine the impact of lixisenatide add-on treatment to basal insulin therapy ± OADs specifically among Asian type 2 diabetes patients. Methods: The proportions of Japanese patients with an unmet need of diabetes management, defined as not achieving an HbA1c < 7% despite having a fasting plasma glucose (FPG) < 130 mg/dL, and without an unmet need, defined as having an endpoint HbA1c < 7%, regardless of FPG level, were determined for the ALOHA study population, which was conducted as a post-marketing survey for insulin glargine in Japan. For the meta-analysis, all Asian modified intent-to-treat patients with baseline and endpoint HbA1c measurements reported from the 3 GetGoal trials were included. Results: Among 1013 Japanese type 2 diabetes patients in the ALOHA study, 36% had an unmet need. In the GetGoal-Duo1, -L, and L-Asia trials, 237 Asian patients were treated with lixisenatide add-on treatment to basal insulin and 226 received placebo. Lixisenatide add-on treatment vs. placebo was associated with the following significant mean changes in efficacy outcomes at week 24: HbA1c: −0.6%, p = 0.005; FPG: −13.3 mg/dL, p = 0.004; PPG: −101.4 mg/dL, p < 0.001; weight: −0.5 kg, p = 0.018; basal insulin dose: −1.6 U, p < 0.001. Conclusions: Lixisenatide add-on treatment may provide a viable option to address the unmet need of basal insulin therapy among Asian type 2 diabetes patients.